The Impact of the Regulatory Reform Process on R&D Investment of European Electricity Utilities - Stephan Schmitt; Denes Kucsera (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The aim of this paper is to give deeper insights into the impact of regulatory reforms and privatization on R&D spending of electricity utilities. Building on a panel data set including the biggest European utilities from eight EU-countries over a period from 1985 until 2010, we find a strong negative influence of privatization and also a negative overall impact of regulation on R&D investment. Nearing competition has a dampening effect on R&D spending, but once the market and regulatory framework conditions have been established, higher levels of competition positively influence R&D. Our results further indicate that the relation between competition and innovative investment can be described as inverted U-shaped. Finally, we could not find any evidence that (ownership) unbundling and incentive regulation affect R&D expenditures of the utilities.
Keywords: L43; L51; L94; 330